Back Cover: Control of Product Distribution and Mechanism by Ligation and Electric Field in the Thermal Activation of Methane (Angew. Chem. Int. Ed. 34/2017). Issue 34 (4th July 2017) - Yue, Lei; Li, Jilai; Zhou, Shaodong; Sun, Xiaoyan; Schlangen, Maria; Shaik, Sason; Schwarz, Helmut
Abstract : Nonselective methane activation can be changed to a highly selective process as a result of the dipole field of a single acetonitrile ligand attached to bare ZnO + . The ligand effect can be modeled well by an oriented external electric field of a negative point charge. In their Communication onpage 10219 ff., H. Schwarz, S. Shaik, and co‐workers provide more details.